2002
DOI: 10.1292/jvms.64.1071
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Intimin- and Shiga Toxin-Producing Escherichia coli from Gulls, Pigeons and Broilers in Finland.

Abstract: ABSTRACT. The role of birds as sources of Shiga toxin-and intimin-producing Escherichia coli was studied. Fecal samples from live gulls (n=86), pigeons (n=33) and broiler chickens (n=199) from 23 flocks were analyzed for stx and eae by PCR. No stx positive samples were detected. In contrast, eae E. coli were highly prevalent among gulls (40%), and was also found in pigeons (7%) and chickens (57% of the flocks contaminated). The eae positive isolates were analyzed genetically and O-serogrouped. One isolate from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
56
4
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 16 publications
(10 reference statements)
15
56
4
5
Order By: Relevance
“…According to our mPCR results, 10 (77%) of the 13 isolates had only the eaeA gene (intimin). Comparing our results on the presence of a virulence gene, similar results were found by Kobayashi et al (22) in Finland, i.e. 29 (15%) out of 199 broiler samples were positive for the eaeA gene, and also in Korea by Oh et al (23), who reported that the eaeA gene was found in 30 E. coli strains obtained from cloacal samples of 184 chicken flocks.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…According to our mPCR results, 10 (77%) of the 13 isolates had only the eaeA gene (intimin). Comparing our results on the presence of a virulence gene, similar results were found by Kobayashi et al (22) in Finland, i.e. 29 (15%) out of 199 broiler samples were positive for the eaeA gene, and also in Korea by Oh et al (23), who reported that the eaeA gene was found in 30 E. coli strains obtained from cloacal samples of 184 chicken flocks.…”
Section: Discussionsupporting
confidence: 91%
“…Intimin is required for human and animal intestinal mucosal colonization of enterohemorrhagic E. coli (7,22,23). According to our mPCR results, 10 (77%) of the 13 isolates had only the eaeA gene (intimin).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Pigeons could be able to carry many pathogenic virus, bacteria, fungus and protozoa for humans and animals without causing any diseases in themselves 1,5,7,10,16 . Domestic pigeons are one of the most important vehicle for spreading of zoonotic infections 16 .…”
Section: Discussionmentioning
confidence: 99%